2022
DOI: 10.1002/cam4.5079
|View full text |Cite
|
Sign up to set email alerts
|

MARCKSL1 interacted with F‐actin to promote esophageal squamous cell carcinoma mobility by modulating the formation of invadopodia

Abstract: Background Emerging evidence indicates that myristoylated alanine‐rich C kinase substrate like 1 (MARCKSL1) is involved in the progression of esophageal squamous cell carcinoma (ESCC). However, the underpinning mechanism is unclear. Here, we investigated the mechanisms involving MARCKSL1 in ESCC progression. Methods CCK8, Transwell and wound‐healing assays were employed to test the effect of MARCKSL1 on proliferation, invasion and migration in vitro. Next, transcriptome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…MARCKS, known as myristoylated alanine-rich C kinase substrate, is an autophagy-related gene. Previous investigations have identified it as a diagnostic marker for gastric cancer ( 93 ), and has also been shown to enhance cell migration and invasion by interacting with F-actin and ECM degradation ( 94 ). Similarly, Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…MARCKS, known as myristoylated alanine-rich C kinase substrate, is an autophagy-related gene. Previous investigations have identified it as a diagnostic marker for gastric cancer ( 93 ), and has also been shown to enhance cell migration and invasion by interacting with F-actin and ECM degradation ( 94 ). Similarly, Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…As a protein associated with the occurrence and development of various tumors, MARCKSL1 has been mainly verified as a potential tumor marker or a new therapeutic target in lung cancer 21 24 , liver cancer 25 27 , colorectal cancer and other tumors. In addition, there are ongoing studies on prostate cancer 28 , breast cancer 29 , 30 , esophageal cancer 31 , basal cell carcinoma 32 , squamous cell carcinoma 33 and other tumors, and their potential as markers is gradually attracting the attention of researchers. MARCKSL1 has been selected as a potential marker for distinguishing metastatic and nonmetastatic sporadic colorectal cancer (sCRC) and is highly expressed in patients with metastatic sCRC.…”
Section: Discussionmentioning
confidence: 99%
“…F-actin is a functional structure for cell mobility. Myristoylated alanine-rich C kinase substrate like 1 (MARCKSL1) relies on its interaction with F-actin to strengthen the mobility of esophageal carcinoma cells [ 16 ]. Moreover, previous study demonstrated that local membrane protrusions by directed polymerization in anterior F-actin triggers cell migration [ 17 ].…”
Section: Discussionmentioning
confidence: 99%